Consideraciones metafísicas de la naturaleza en Santo Tomás de Aquino - Ponce, Manuel Ocampo (Sapientia, 2017)
Given the applicability of the notion of nature to any philosophical, theological, moral, juridical discussion, etc., this work is an attempt to deepen the concept of nature as a principle of movement in the thought of St. Thomas Aquinas. Taking advantage of the philosophical legacy of St. Thomas and with the rigor and metaphysical precision which characterizes it, we intend to deepen the essential metaphysical notes of nature and its relationship with knowledge. The vision of nature as objective reality, and the concept of nature as universal in the human mind; also the passage from the physical to the metaphysical plane. It also becomes clear that for St. Thomas the source of all dynamism can be none other than the being of beings, that is, the fact that being is necessary in the understanding of nature as the principle of operations of all creatures.